sin 1 0 ∘ 1 − cos 1 0 ∘ 3 = ?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Indeed :
( 2 1 cos ( 1 0 ∘ ) − 2 3 sin ( 1 0 ∘ ) ) = sin ( 3 0 − 1 0 ) = sin 2 0
No need to use sin ( π − x ) = sin x , otherwise I was writing the exact same solution. BTW (+1) :-)
I used c o s 6 0 c o s 1 0 − s i n 6 0 s i n 1 0 = c o s 7 0 and, s i n 2 0 = c o s 7 0 A fan of 'cosine', ain't I?
Still a bit unsure why sin 160 / sin 20 = 1 Which identity allows this to be true?
Log in to reply
We can use the formula
sin ( a − b ) = sin ( a ) cos ( b ) − cos ( a ) sin ( b )
with a = 1 8 0 ∘ and b = 2 0 ∘ , giving us that
sin ( 1 6 0 ∘ ) = sin ( 1 8 0 ∘ − 2 0 ∘ ) = sin ( 1 8 0 ∘ ) cos ( 2 0 ∘ ) − cos ( 1 8 0 ∘ ) sin ( 2 0 ∘ ) =
0 ∗ cos ( 2 0 ∘ ) − ( − 1 ) ∗ sin ( 2 0 ∘ ) = sin ( 2 0 ∘ ) .
Relevant wiki: Sum and Difference Trigonometric Formulas - Problem Solving
sin 1 0 ∘ 1 − cos 1 0 ∘ 3 = sin 1 0 ∘ 2 × 2 1 − cos 1 0 ∘ 2 × 2 3 = 2 ( sin 1 0 ∘ sin 3 0 ∘ − cos 1 0 ∘ cos 3 0 ∘ ) = 2 ( sin 1 0 ∘ 3 sin 1 0 ∘ − 4 sin 3 1 0 ∘ − cos 1 0 ∘ 4 cos 3 1 0 ∘ − 3 cos 1 0 ∘ ) = 2 ( 3 − 4 sin 2 1 0 ∘ − 4 cos 2 1 0 ∘ + 3 ) = 2 ( 6 − 4 ) = 4
sin10=cos80=cos2(40) =2(cos40)^2-1. =2×(2cos^2(20)-1)^2-1. =2×(4cos^4(20)-4cos^2(20)+1)-1. =8cos^4(20)-8cos^2(20)+2-1 =8cos^2(20){cos^2(20)-1}+1. =8(1-2sin^2(10))^2{(1-2sin^2(10))^2-1}+1. Put sin10=X.above formula will be like this ,x= 8(1-4x^2+4x^4)(1-4x^2+4x^4-1)+1 so 128x^8-256x^6+160x^4-32x^2-x+1=0. by trying & error X=sin10=nearly .173648 so cos10=(1-.173648^2)^.5=.9848078 so the expression =(1÷(.173648))-(√3÷.9848078)=4.000005
Problem Loading...
Note Loading...
Set Loading...
Relevant wiki: Sum and Difference Trigonometric Formulas - Problem Solving
This can be written as
sin ( 1 0 ∘ ) cos ( 1 0 ∘ ) 1 ∗ cos ( 1 0 ∘ ) − 3 ∗ sin ( 1 0 ∘ ) = 2 sin ( 1 0 ∘ ) cos ( 1 0 ∘ ) 4 ∗ ( 2 1 cos ( 1 0 ∘ ) − 2 3 sin ( 1 0 ∘ ) ) =
sin ( 2 0 ∘ ) 4 ∗ ( sin ( 1 5 0 ∘ ) cos ( 1 0 ∘ ) + cos ( 1 5 0 ∘ ) sin ( 1 0 ∘ ) ) = sin ( 2 0 ∘ ) 4 sin ( 1 6 0 ∘ ) = 4 ,
since sin ( x ) = sin ( 1 8 0 ∘ − x ) .